2017
DOI: 10.1155/2017/2438247
|View full text |Cite
|
Sign up to set email alerts
|

Maresin 1 Mitigates High Glucose-Induced Mouse Glomerular Mesangial Cell Injury by Inhibiting Inflammation and Fibrosis

Abstract: Background. Inflammation and fibrosis are the important pathophysiologic processes in diabetic nephropathy (DN). Maresin 1 is a potential anti-inflammatory lipid mediator, which has displayed powerful proresolving activities. Aim. We determine whether maresin 1 has protective effect on mouse glomerular mesangial cells (GMCs) induced by high glucose. Methods. We cultured GMCs stimulated by high glucose and categorized as follows: normal glucose group (5.6 mmol/L), high glucose group (30 mmol/L), mannitol group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…However, we did not find macrophages in renal cortex of DN mice model. 29 Our study showed that in renal biopsy samples of DN patients and renal cortex of DN mice, expression levels of TGF-β1 and other inflammatory factors increased as ChemR23 was elevated. It was suggested that chronic inflammation played a crucial role in the occurrence and development of DN.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, we did not find macrophages in renal cortex of DN mice model. 29 Our study showed that in renal biopsy samples of DN patients and renal cortex of DN mice, expression levels of TGF-β1 and other inflammatory factors increased as ChemR23 was elevated. It was suggested that chronic inflammation played a crucial role in the occurrence and development of DN.…”
Section: Discussionmentioning
confidence: 56%
“…In DN, elevated expression of TGF-β1 was often accompanied by gradual fibrosis and finally led to renal failure. 29 Our study showed that in renal biopsy samples of DN patients and renal cortex of DN mice, expression levels of TGF-β1 and other inflammatory factors increased as ChemR23 was elevated.…”
Section: Serum Chemerin Level Was Closely Related With Renal Functionmentioning
confidence: 56%
“…Finally, previous studies showed that MaR1 decreased ROS levels during lung I/R Injury [40]. The expression of ROS increased in the presence of high glucose group, but it decreased after the treatment with MaR1 at different concentrations [41]. Another study showed that ROS levels were decreased by treatment of MaR1 in Carbon Tetrachloride-Induced Liver Injury in Mice [42].…”
Section: Discussionmentioning
confidence: 80%
“…MaR-1 is effective in controlling inflammation in periodontal infections with unresolved inflammation and leukocyte-mediated tissue destruction (108), and restoring the reparative function of nonhealing diabetic wounds impaired the macrophages (109). MaR-1 has also been tested in the treatment of diabetic nephropathy by inhibiting nucleotide binding and oligomerization domain-like receptor family pyrin domain-containing-3 and controls the inflammation rate in renal failure (110).…”
Section: Mars As Therapeutic Targetsmentioning
confidence: 99%